دراسة بيوستراتغرافية لتوضعات الميوسين الأوسط في الجزء الشمالي من حوض نهر الكبير الشمالي (مجلة جامعة اللاذقية - سلسلة العلوم الأساسية, 2017)
تتواجد توضعات الميوسين الأوسط على شكل تكشفات محدودة المساحة في الأطراف الشمالية من حوض نهر الكبير الشمالي وتتميز بتغيرات كبيرة وسريعة في السماكة والسحنة. لقد تركزت هذه الدراسة على نتائج التحليل المستحاثي الدقيق لـ 41 عينة (قاسية وطرية) مأخوذة من ثلاث مقاطع جيولوجية، تم من خلالها تأكيد النطاقات الرئيسية المميزة للميوسين الأوسط اعتماداً على المنخربات البلانكتونية وهي:N9, -Orbulina suturalis-Globerotalia peripherorondaN10-N13-Globerotalia fohsi, Sphaaerodinellopsis subdehiscens- Globigrina drury N14 – Globigerina nepenthes- Globerotalia siakensis.كما تم تحديد المنخربات القاعية التي تميزت بتنوعها وتزايد أعدادها في الأطراف الشمالية للحوض النيوجيني والتعرف على الطبيعة الليتولوجية لهذه التوضعات المؤلفة من تناوبات كلسية حوارية وكلسية مارنية، متوسطة القساوة إلى مارنية طرية جداً ذات ألوان متباينة، كما ساهمت هذه الدراسة في الكشف عن بعض معالم التطورات الباليوجغرافية التي طرأت عل الحوض في تلك الفترة من الزمن .Middle Miocene deposits reveal the form of outcrops which are limited in area on the northern boards of the basin of AL-KABEER Al-Shemaly River. It is characterized by a large and fast changes in thickness and facies.This study focused on the results of careful Fossile analysis of 41 samples (hard and soft) which were taken from the three geological sections, through which the principal zones, which characterize middle Miocene, were confirmed depending on planktonic foraminifera.N9, -Orbulina suturalis-Globerotalia peripherorondaN10-N13-Globerotalia fohsi, Sphaaerodinellopsis subdehiscens- Globigrina drury , N14 – Globigerina nepenthes- Globerotalia siakensis.It was identified as benthic foraminifera, which has been characterized by its diversity and their increasing numbers in the northern boards of the Neogene basin and identify the lithology of these deposits consisting of alternations of limestone and limestone of medium hardness to very soft marl with different colors.This study also contributed to the detection of some paleogeographical development in the basin in that period of time.